Interactions of substrates and phosphinyl containing inhibitors with bacterial and human zinc proteases - Fatema Amatur Rahman; Imin Wushur; Ida Kristine Østnes Hansen; Tor Haug; Klara Stensvåg; Bibek Chaulagain; Tra-Mi Nguyen; Olayiwola Adedotun Adekoya; Nabin Malla; Jan-Olof Winberg; Ingebrigt Sylte (PLoS ONE, 2025)
Inhibitors of bacterial virulence is suggested to be a promising strategy in the fight against bacterial resistance. The zinc metalloproteases (MPs) thermolysin (TLN), pseudolysin (PLN, LasB) and aureolysin (ALN) are bacterial virulence factors from the M4 family of proteases structurally resembling human zinc MPs. Knowledge about the binding modes of substrates and inhibitors with the bacterial and human zinc MPs is therefore fundamental for developing inhibitors without strong off-target effects. In the present paper, we studied the molecular interactions and cleavage of TLN, the prototype enzyme of the M4 family, with the substrate Mca-Arg-Pro-Pro-Gly-Phe-Ser-Ala-Phe-Lys(Dnp)-OH (ES005) by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) and molecular dynamics (MD) simulations. Enzyme inhibition kinetic studies were used to test 5 compounds (H-1 - H-5) containing phosphinyl as the zinc binding group for their inhibition of TLN, PLN and ALN and of the human matrix metalloproteases MMP-9 and MMP-14. The MALDI-TOF MS results revealed that TLN cleaves ES005 at three sites. The most abundant cleavages were between Ala and Phe, and between Gly and Phe, while the third was between Ser and Ala. MD simulations with Ala or Gly in the S1 subpocket and Phe in S1’ subpocket gave stable interactions between ES005 and TLN. The MD simulations with Ser in the S1 subpocket and Ala in the S1’ subpocket showed larger movements of the substrate relative to the catalytic site than the others, which may explain that the Ser-Ala cleavage product was less abundant than the cleavage products from Ala-Phe and Gly-Phe. H-1 inhibited MMP-14 and MMP-9 with inhibition constants ranging from 0.89 to 30 μM but did not inhibit the bacterial zinc MPs. Induced fit docking showed that the aromatic group of H-1, that entered the S1’ subpocket of the human MMPs, is too big for the S1’ subpocket of the bacterial zinc MPs. H-2 inhibited the human MMPs with inhibition constants ranging from 0.53 μM (MMP-9) to 3.0 μM (MMP-14) and the bacterial zinc MPs with inhibition constants ranging from 2.5 μM (TLN) to 80 μM (ALN). Induced fit docking indicated that H-2 interacted quite differently with the human and bacterial zinc proteases, but with primed and unprimed subpockets in both. H-3, H-4 and H-5 did not inhibit any of the zinc MPs with inhibition constants < 100 μM. The MD simulations of ES005 with TLN showed that the MALDI-TOF MS results could be explained by that a Phe in S1’ subpocket generate more stable interaction with TLN than an Ala in that subpocket. The docking studies indicated that the size of the S1’ subpocket is an important determinant for inhibitor selectivity between bacterial and human zinc MPs.